Digital Marketing Training At The Tempe Tofu Business Association - Haerah, Kahar; Arifin, Zainul (Journal Of Humanities Community Empowerment, 2024)
This article discusses the results of community service activities in Kebonsari Village, especially at the Tempe Tofu Business Association (PUTT) in Talangsari Village. PUTT is an initiative that aims to create jobs and improve the welfare of its members. One of the key aspects of PUTT's success is the understanding of community members towards digital marketing. Digital marketing is explained as a strategy to market products through various digital media such as the internet, telephone, and television. The application of digital marketing is important in the current context, which is filled with digital technology, providing an effective way to expand market reach and increase the competitiveness of micro, small, and medium enterprises (MSMEs) such as PUTTia